Cardio-Oncology : The Clinical Overlap of Cancer and Heart Disease - Kimmick, Gretchen G.; Lenihan, Daniel J.; Sawyer, Douglas B.; Mayer, Erica L.; Hershman, Dawn L. (Springer International Publishing : Imprint: Springer, 2017)
Co-edited and written by an interdisciplinary team of experts in oncology and cardiology, this book is a clinically useful resource on these overlapping topics: - Cardiac complications in patients receiving cancer therapy - The treatment of cancer in patients with cardiovascular disease - The treatment of cardiovascular disease in patients with cancer When relevant to medical practice, epidemiology and basic science are also included in the discussion and each chapter is written by an oncologist and a cardiologist. Additionally, the chapters follow a similar format to make the book truly interdisciplinary, user-friendly, and clinically applicable to specialists and non-specialists who care for patients with both cancer and cardiovascular disease.
Keywords: Medicine.; Cardiology.; Oncology.; Primary care (Medicine).; elektronické knihy; electronic books